Results on quiescent and post-disruption runaway electrons studies at Frascati Tokamak Upgrade: RE mitigation via solid deuterium pellets and anomalous Doppler instability. (13th October 2021) - Carnevale, D.; Buratti, P.; Bin, W.; Bombarda, F.; Boncagni, L.; Duval, B.; Esposito, B.; Ceccuzzi, S.; Calacci, L.; Baruzzo, M.; Cappelli, M.; Castaldo, C.; et al.
Abstract: Results from the last FTU campaigns on RE mitigation strategies for quiescent and post-disruption RE beams are presented. We provide experimental evidence that for some RE quiescent scenarios D2 solid pellets achieve complete RE suppression capability, mainly due to the induced burst MHD activity expelling RE seed, whereas in other cases we report clear indications of avalanche multiplication of RE. Results on the assimilation of solid deuterium pellets on RE quiescent scenarios are provided. Quantitative indications of dissipative effects of anomalous Doppler instabilities (ADI) and MHD activity, in terms of critical electric field increase, is introduced and supported by experimental evidence. Multiple analysis are provided to show the significant energy conversion/dissipation of large ADI on post-disruption RE beams suggesting new strategies for RE energy suppression. We also demonstrate experimentally that modulated ECRH could be used for ADI pacing.